Differential Effects of the COVID-19 Lockdown and Regional Fire on the Air Quality of Medellín, Colombia - Juan J. Henao; Angela M. Rendón; K. Santiago Hernández; Paola A. Giraldo-Ramirez; Vanessa Robledo; Jose A. Posada-Marín; Natalia Bernal; Juan F. Salazar; John F. Mejía (Atmosphere, 2021)
Governments’ responses to the COVID-19 pandemic provide a unique opportunity to study the effects of restricted socioeconomic activity on air quality. Here, we study the changes in air pollution levels during the lockdown in Medellín and its metropolitan area, Colombia, for periods with and without enhanced regional fire activity, considering the effects of meteorology using random forest and multiple linear regression methods. The lockdown measures, which reduced mean traffic volume by 70% compared to 2016–2019, resulted in reductions for PM2.5 (50–63%), PM10 (59–64%), NO (75–76%), NO2 (43–47%), and CO (40–47%), while O3 concentration increased by 19–22%. In contrast, when fire activity was high, the effects of the lockdown on air quality were shadowed by the long-range transport of biomass burning emissions, increasing fine particulate matter and ozone. This study shows that healthier levels are achievable through significant efforts from decision-makers and society. The results highlight the need to develop integral measures that do not only consider reductions in the local emissions from transportation and industry, but also the role of fire activity in the region, as well as the difficulties of achieving reductions in ozone from measures that are effective at reducing primary pollutants.